Causative Agents and Susceptibility of Antimicrobials among Suspected Females with Urinary Tract Infection in Tertiary Care Hospitals of Western Nepal - Thapa, P; Parajuli, K; Poudel, A; Thapa, A; Manandhar, B; Laudari, D; Malla, HB; Katiwada, R (Journal of Chitwan Medical College, 2013)
Urinary Tract Infection (UTI) is a common and serious health problem affecting many people each year around the World especially females. Therapy of UTI relies on the predictability of the agents causing UTI and knowledge of their antimicrobial susceptibility patterns. A retrospective cross-sectional study was conducted in two major hospitals of Western Nepal. Tools for data collection were a data collection form. Total 400 patient’s file with suspected UTI were reviewed, out of which 173 (43.3 %) of the suspected samples showed presence of potential pathogens causing UTI. UTI was mostly prevalent in females of age group 21-30. Escherichia coli (E. coli) was the predominant (65.1%) bacterial pathogen. Amikacin was found to be most sensitive antimicrobial followed by Nitrofurantoin and Gentamcin. Ampicillin showed the higher percentage of resistant, compared to other antimicrobials. As drug resistance among bacterial pathogens is an evolving process, regular surveillance and monitoring is necessary to provide effective treatment of UTIs. DOI: http://dx.doi.org/10.3126/jcmc.v3i2.8436 Journal of Chitwan Medical College Vol.3(2) 2013 16-19